BOOK REVIEW - Mhlauli, Mavis B. (Advances in Social Sciences Research Journal, 2016)
The book under review was written by Ayers, William (2001) and is entitled “To Teach: The journey of a teacher” (2nd Ed). The first edition of this book was published in 1993 and won an award for distinguished written work. When writing this book William Ayers was a Professor of Education at the University of Illinois, Chicago, United States of America (USA). He has taught students at various levels in elementary schools and colleges. His writings are inspired largely by his experiences with young children as a teacher and father to his three sons.